Comparison of Serum Apelin-36 and Insulin Resistance between Male and Female Type 2 Diabetics - Mohammed, Maryam Moayad; Khaleel, Fayhaa M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Diabetes mellitus (DM) is a chronic metabolic disorder characterized by persistent hyperglycemia. It may be due to impaired insulin secretion, resistance to insulin’s peripheral actions, or both. The aim of this study was to estimate the percentage impact of obesity on the incidence of DM, as well as compare the levels of Apelin-36, glutathione-S-transferase, and insulin resistance (IR) in subjects with and without DM for both sexes. This study included 120 subjects, divided into 60 as a control group and 60 as a patient group of both sexes; all were adults between the ages of 30 and 65. The participants with fasting blood sugar, lipid profile, glycated hemoglobin (HbA1c), apelin-36, body mass index, insulin hormone, and IR were tested. The results showed a significant difference in the males’ age and body mass index but a non-significant difference for females. Fasting blood sugar, HbA1c and Apelin-36, insulin hormone, and IR for both sexes have a significant difference (P ≤ 0.05). There is no relation between glutathione-S-transferase activity, insulin, and IR for both sexes’ correlation; the area under the curve in the study= 0.993, indicating a perfect ROC test for correctly identifying individuals. An important role is played by higher levels of Apelin-36, which directly increase obesity and DM. This study concluded that Apelin-36 serves as a reliable indicator for both male and female patients with type 2 DM (T2DM); while women are less likely to develop DM, they are more likely to experience common complications such as cardiovascular disease. Men are more likely to develop T2DM due to their age and higher weight than women.